A nitrogen-rich hyperbranched polymer as cathode encapsulated material for superior long-cycling lithium-sulfur batteries. (10th January 2020) - Liu, Xu; Chen, Pingping; Chen, Jie; Zeng, Qinghui; Wang, Zhinan; Li, Zengxi; Zhang, Liaoyun
Abstract: The shuttle effect of Lithium-sulfur (Li–S) batteries often leads to poor long-cycling performance. Finding a more effective way to suppress the shuttle effect of lithium sulfur battery is still a huge challenge. Herein, a novel polymer encapsulated layer (HPEIGA) was synthesized by a one-step reaction of hyperbranched polyethyleneimine (HPEI) and Glutaraldehyde. The HPEIGA can not only like the traditional encapsulated layer that has the physical barrier effect for inhibiting the dissolution of the polysulfide. More importantly, large amount of nitrogen atoms in HPEIGA can adsorb polysulfide anions by chemical interaction, which can effectively suppress polysulfide shuttling effect. As a result, the shuttling current of the cell based on the encapsulated carbon-nanotube/sulfur (CNT-S) electrode (HPEIGA@CNT-S) is merely 1/8 that of CNT-S electrode without encapsulated layer. Furthermore, the capacity retention of the HPEIGA@CNT-S cell can reach up 73.68% with a small decay of 0.043% per cycle at the current of 2C even after 600 cycles. Thus, nitrogen-contained hyperbranched polymer has a great potential as encapsulated layer of sulfur electrode for high performance Li–S batteries. Graphical abstract: Image 1 Highlights: A hyperbranced polymer encapsulated layer for sulfur cathode was synthesized. The preparation process of encapsulated layer is rapid and without catalyst. This encapsulated layer effectively retards shuttle effect of polysulfide. The resulted cell exhibited capacity retention of 73.68% after 600 cycles.